Solubility and Bioavailability Enhancement of Poorly Aqueous Soluble Atorvastatin: In Vitro, Ex Vivo, and In Vivo Studies - Rodde, Madhuri S. (Hindawi Publishing Corporation, 2014)
The objective of this investigation was to improve the solubility of the poorly water soluble drug atorvastatin (ATR), using solid dispersion (SD) techniques, with Neem Gum (NG) as a hydrophilic carrier. The effects of the polymer concentration and method of preparation on the solubility and dissolution rate were studied. The results showed that the solubility of ATR increases with increasing NG concentration. However, dissolution rate of ATR from its SD was dependent on the method used to prepare SD. An in vitro drug release study revealed that the solvent evaporation technique is a more convenient and effective method of preparing SD than kneading method. The SD was characterized using DSC, SEM, and XRD study. An in vivo study was performed in which the 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMG CoA) reductase inhibition activity was measured. A significant reduction in HMG CoA reductase activity was observed with SD of ATR compared with the plain drug. An ex vivo absorption study was carried out using modified apparatus developed in our laboratory. The in vitro drug release and in vivo and ex vivo studies clearly demonstrated the potential of hydrophilic NG in enhancing the solubility, dissolution rate, and bioavailability of ATR.